Promoting international co-operation in the age of global space governance – A study on on-orbit servicing operations - Chiu, S (Elsevier, 2018)
Outer space exploration has been an area where the international community demonstrated a significant level of co-operation, successfully transcending geographical, national and cultural boundaries. In the age of global governance, international co-operation has never been more important in resolving today’s global challenges. One of such challenges is the growing amount of space debris in orbits, which, if unresolved, will not only undermine global information and communications technology (ICT) system, but will also hinder areas of sustainable development where outer space activities contribute to. (e.g. satellite imaging for disaster warning and management, satellite imaging for agricultural purpose) This paper proposes to conceptualize space orbit and radio frequency as an essential global commons, whose governance requires international co-operation. In examining potentials and challenges in moving forward space orbit governance, the paper pays particular focus on ensuring space safety and sustainability through the introduction of on-orbit servicing (OOS) operations. The paper will identify aspects of OOS that warrant further collaborations, specifically, the standardization of docking and rendez-vous practices that could facilitate future space activities. Recognizing the potential of future commercialization of refueling, repairing and debris removal operations in orbits, this paper argues that standardization practices would be the first step towards enhancing international co-operation, as well as in strengthening the existing regime of peaceful use of outer space. Ultimately, it could play a role in addressing one of today’s most imminent challenges – ensuring sustainable use of global commons.